2018
DOI: 10.1055/s-0038-1675209
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Uterine Artery Doppler for the Prediction of Preeclampsia in Nulliparous Women: The Great Obstetrical Syndrome Study

Abstract: Preeclampsia (PE) is a multisystem disorder of pregnancy defined by the combination of new-onset hypertension and proteinuria that contribute substantially to perinatal morbidity and mortality worldwide. 1,2 The etiology of PE remains controversial but it is now recognized that alterations in the growth and development of placental villi and their underlying vasculature play an important role in the pathogenesis of the disease. 3 The physiological transformation of uterine spiral arteries by the cytotrophoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…As regards BMI, our results were in agreement with the study of Demers et al (13) , as they reported significant difference between both groups in the BMI values. However, Liu et al (14) reported that age showed significant difference among eclampsia cases and controls.…”
Section: Discussionsupporting
confidence: 93%
“…As regards BMI, our results were in agreement with the study of Demers et al (13) , as they reported significant difference between both groups in the BMI values. However, Liu et al (14) reported that age showed significant difference among eclampsia cases and controls.…”
Section: Discussionsupporting
confidence: 93%
“…High UtA‐PI in the second and third trimesters of pregnancy is related to the risk of preeclampsia and SGA 3 . In the first trimester, the accuracy of UtA‐PI for prediction of preeclampsia is reportedly controversial 4–8 . Demers et al 5 and Melchiorre et al 4 reported that the first trimester UtA‐PI was associated with the risk of preterm preeclampsia but not with the risk of term preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…In the first trimester, the accuracy of UtA‐PI for prediction of preeclampsia is reportedly controversial 4–8 . Demers et al 5 and Melchiorre et al 4 reported that the first trimester UtA‐PI was associated with the risk of preterm preeclampsia but not with the risk of term preeclampsia. Since UtA‐PI cannot assess the placental circulation in real time, it seems to show significant changes only after at least two‐thirds of the placental vascularization is affected 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, our study found that uterine artery PI could predict PE at a sensitivity and specificity of 81.3 % and 72.2 %. However, in the study of Demers et al [20] , first-trimester uterine artery [UtA] pulsatility index [PI] was associated with preterm but not with term PE. However, in the study of Myatt et al [21] , uterine artery Doppler measurements prior to 21 weeks of gestation [median 16.6 weeks] showed low (poor) sensitivity for prediction of preeclampsia overall in a well-characterized, low-risk, nulliparous females.…”
Section: Disucssionmentioning
confidence: 99%